MENJAGA KEUTUHAN BANGSA - Chaer, Moh. Toriqul (FENOMENA, 2016)
Indonesia is a pluralistic nation (plural). Multiculturalism beckons the existence of plurality and difference. Understanding and management of pluralism and multiculturalism will generate a positive force for the development of the nation. Conversely, if it is not understood and managed properly, diversity and multiculturalism could be a destructive factor andÂ Â a disaster trigger. Conflict and social violence that often occurs between groups of people are part of plurality and multiculturalism are not managed properly. Religious conflict as happened in Maumere (1995), Surabaya, Situbondo and Tasikmalaya (1996), Rengasdengklok (1997), Jakarta, Solo and Kupang (1998), Poso, Ambon (1999-2002), are not bit fatalities, but also has destroyed hundreds of places of worship (both churches and mosques) burned and destroyed. Similarly, notes of ethnics violence, such as certain ethnic violence in West Kalimantan (1933), Central Kalimantan (2000), it is needed a preventive measures as early prevention, so that such events do not recur in the future.Â To achieve this goal, inclusive-instrinsic understanding of religion.. Borrowing aÂ term of Malinowskiâs thinkingÂ wishfull;Â theirÂ beliefsÂ are considered nilÂ even thoughÂ the truth of religion, butÂ religionÂ is still positive that was able to help the frustration and still has the potential to realize the social unity.